Treatment planning system and patient positioning for boron neutron capture therapy - Kumada, Hiroaki; Takada, Kenta (Therapeutic Radiology and Oncology, 2018)
To perform boron neutron capture therapy (BNCT), a type of radiotherapy, a neutron source as a treatment device and peripheral devices such as a treatment planning system (TPS), patient setting device, and neutron monitor are needed. In particular, a TPS is indispensable software in radiotherapy and enables the simulation of a treatment with neutron beam irradiation with a patient’s three-dimensional model based on the patient’s medical images. In addition, the system supports the determination of suitable irradiation conditions for each patient. The patient setting device works to realize the irradiation conditions determined during treatment planning in the actual irradiation room just before irradiation.